2006
DOI: 10.1103/physreva.73.022715
|View full text |Cite
|
Sign up to set email alerts
|

Optical analog of Rabi oscillation suppression due to atomic motion

Abstract: The Rabi oscillations of a two-level atom illuminated by a laser on resonance with the atomic transition may be suppressed by the atomic motion through averaging or filtering mechanisms. The optical analogs of these velocity effects are described. The two atomic levels correspond in the optical analogy to orthogonal polarizations of light and the Rabi oscillations to polarization oscillations in a medium which is optically active, naturally or due to a magnetic field. In the later case, the two orthogonal pola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The second class of optical analogues mimics coherent effects of atoms or molecules driven by laser fields, such as Rabi oscillations and adiabatic rapid passage [61][62][63][64][65], population trapping and coherent population transfer like Stimulated Raman adiabatic passage [66][67][68][69][70][71][72][73][74][75], stabilization of atoms in ultrastrong laser fields [76][77][78][79], the optical analogue of the Franck-Condon principle [10], and electromagnetically-induced transparency [80][81][82][83][84].…”
Section: Overview On Quantum-optical Analogiesmentioning
confidence: 99%
“…The second class of optical analogues mimics coherent effects of atoms or molecules driven by laser fields, such as Rabi oscillations and adiabatic rapid passage [61][62][63][64][65], population trapping and coherent population transfer like Stimulated Raman adiabatic passage [66][67][68][69][70][71][72][73][74][75], stabilization of atoms in ultrastrong laser fields [76][77][78][79], the optical analogue of the Franck-Condon principle [10], and electromagnetically-induced transparency [80][81][82][83][84].…”
Section: Overview On Quantum-optical Analogiesmentioning
confidence: 99%
“…Therefore, some interesting researches on atomic motion have been carried out [29][30][31][32][33][34]. These researches have shown that the atomic motion and the field-mode structure can bring about the nonlinear transient effects of atomic population [29], control the entanglement and realize the quantum gate operation [30], influence quantum fluctuations of a single atom in a weakly driven cavity [31], and suppress the Rabi oscillations of an atom irradiated by a laser in resonance with the atomic transition [32]. Our previous study has found that the atomic motion changes the time to create a Schr¨ dinger cat state [35].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the intuitive demonstration of classical analogues of quantum phenomena of which many of them are related to condensed matter systems, the techniques of optoquantum analogies have been extended to the field of quantum optics to simulate the interesting phenomena like quantum Rabi oscillations [17,18], stabilization of atoms in ultrastrong laser fields [19,20], stimulated Raman adiabatic passage [21][22][23][24][25][26][27] linked with coherent population trapping (CPT) [11,28,29], quantum state embedded in a continuum accompanied by Fano resonance [28,[30][31][32], electromagnetically induced transparency [33][34][35][36][37][38], coherent population dynamics in a three-level atomic system at the condition of two photon resonance required for CPT [39], quantum information processing [40] and quantum teleportation [41].…”
Section: Introductionmentioning
confidence: 99%